Synthesis, Characterization, and Antibacterial effect of Complexes lead(II) and Tin (II) With (L-leucin and 8-hydroxyquinoline) - Taghreed H. Al- Noor; Shifaa Jameel Ibraheem (Al-Qadisiyah Journal of Pure Science, 2017)
The research includes the synthesis and identification of two types complexes of M+2 Ions using amino acid(L-leucin) and 8-hydroxyqinoline as ligands in general compositions [ M (Leu)2] and[ M (Q)2] were L-leucin (C6H13NO2)symbolized as (LeuH), and 8-hydroxyqinoline,(C9H7NO2) symbolized as(8-HQ) ,M(II) =Sn(II) and Pb(II), The ligand and metal ions were brought into reaction in ethanolic mediumusing (1:2) metal : ligand molar ratios as required.Products were found to be solid crystalline complexes, which have been Characterized through thefollowing techniques: Melting points, Solubility, Molar conductivity. Determination the percentage of themetal in the complexes by (Atomic Absorption Spectrometry). chloride ion content were also evolution by(mohr method) . Spectroscopic Methods [FT-IR and UV-Vis]. The proposed structure of the complexes usingprogram , chem office 3D(2006)